2014
DOI: 10.1021/jp407388h
|View full text |Cite
|
Sign up to set email alerts
|

Decoration of WS2 Nanotubes and Fullerene-Like MoS2 with Gold Nanoparticles

Abstract: A new technique of gold nanoparticle (AuNP) growth on the sidewalls of WS2 inorganic nanotubes (INT-WS2) and the surface of MoS2 fullerene-like nanoparticles (IF-MoS2) is developed to produce metal–semiconductor nanocomposites. The coverage density and mean size of the nanoparticles are dependent on the HAuCl4/MS2 (M = W, Mo) molar ratio. AuNPs formation mechanism seems to involve spatially divided reactions of AuCl4 – reduction and WS2/MoS2 oxidation taking place on the surface defects of the disulfide nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
61
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 68 publications
5
61
0
Order By: Relevance
“…1(d)). The same behavior was previously observed for gold nanoparticles grown on NT-WS 2 [32]. The local composition of the Ag-NT-WS 2 nanocomposite prepared using AgNO 3 was also visualized using STEM-EDX mapping (Fig.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…1(d)). The same behavior was previously observed for gold nanoparticles grown on NT-WS 2 [32]. The local composition of the Ag-NT-WS 2 nanocomposite prepared using AgNO 3 was also visualized using STEM-EDX mapping (Fig.…”
Section: Resultssupporting
confidence: 75%
“…On the contrary, the functionalization of NT-WS 2 with plasmonic silver nanoparticles has not been studied yet, despite several attempts having been made to synthesize Au-NT-WS 2 nanocomposites [31][32][33][34]. Moreover, it was suggested in our previous work [32], which focused on the functionalization of NT-WS 2 with AuNPs via spontaneous HAuCl 4 reduction on the disulfide surface, that the same technique could be applied using AgNO 3 solutions for the production of Ag-NT-WS 2 nanocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…262 A mechanism involving the oxidation of the molybdenum or tungsten atoms from +IV to +VI has been proposed in the case of WS2 nanotubes and fullerene-like MoS2. 263 Metal deposition on TMDCs monolayers can be controlled by a careful choice of the reducing agents, capping molecules and nature of both the nanosheet and the metal itself to induce an epitaxial growth of the metallic structure on top of the monolayer. 260 More complex phenomena have been recently observed on these TMDC/metal systems, leading to the formation of gold nanowires on MoS2 surfaces 264 , or to the synthesis of TMDC hybrid nanobelts (MoS2, TaS2, TiS2, WSe2 or TaSe2) decorated with Pt or PtAg alloy nanoparticles.…”
Section: O2 For (I) 0 H (Ii) 6 H and (Iii) 24 H Dark Contrast Dots mentioning
confidence: 99%
“…The gold NPs (AuNPs) are among the most intensively studied and applied groups of novel nanomaterials due to their aforementioned properties [20e24]. Pioneering works to anchor or decorate gold NPs to LTMD as well as inorganic nanotubes or fullerenes (INTs or IFs) showed that the NPs could be selectively seated on MoS 2 surfaces through non-covalent bonds [18] or chemical bonds [19,25]. Although growth mechanisms are different, rather small-sized NPs have been reported.…”
Section: Introductionmentioning
confidence: 99%